GOAL AND OBJECTIVES OF MULTIDIDACTICS - Isroilova Odina; Abdurahmonova Zilola (TADQIQOTLAR.UZ, 2023)
Abstract: Multididactic is an educational approach that integrates multiple disciplines and teaching methods to provide a holistic and comprehensive learning experience for students. This approach is based on the principle that learning is more effective when it is connected to real-life experiences and when it is contextualized within a broader framework.Multididactic is often contrasted with traditional educational approaches that focus on individual subject areas and often rely on passive learning, such as lectures and memorization. Instead, Multididactic seeks to create an active and engaging learning environment where students can see the relevance and application of what they are learning.